2015
DOI: 10.12957/rhupe.2015.17774
|View full text |Cite
|
Sign up to set email alerts
|

Ensino de oncologia na graduação médica e autorregulação da aprendizagem

Abstract: Artigo de revisão Resumo O câncer representa uma importante causa de mortalidade e morbidade mundial. A formação profissional em nível superior demanda o desenvolvimento de competências e habilidades que vão além da simples acumulação e aplicação de conhecimentos técnicos e científicos. Considerando a multidimensionalidade da educação médica e a abrangência do escopo de atuação do profissional de medicina, o presente artigo se propõe a analisar as potenciais contribuições da Liga de Oncologia da Universidade d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 20 publications
0
3
0
3
Order By: Relevance
“…As it is a multidisciplinary area that applies to distinct stages of human development, oncology content can be taught in a fragmented way within the curriculum of general disciplines (16,21) . The analysis of the menus of other subjects in the curriculum of nursing courses found that some mandatory subjects have classes dedicated to the pathophysiology, control, prevention and diagnosis of cancer and/or assistance to cancer patients at different stages of human development.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As it is a multidisciplinary area that applies to distinct stages of human development, oncology content can be taught in a fragmented way within the curriculum of general disciplines (16,21) . The analysis of the menus of other subjects in the curriculum of nursing courses found that some mandatory subjects have classes dedicated to the pathophysiology, control, prevention and diagnosis of cancer and/or assistance to cancer patients at different stages of human development.…”
Section: Discussionmentioning
confidence: 99%
“…These activities are implemented according to the organization of each league, and their actions are based on the university tripod (teaching, research, and extension) aiming to complement the academic education in a specific area (26) . Other strategies under implementation are the research and extension projects that stimulate the education and the scientific production in oncology, aiming to reduce the gaps in academic and professional qualification in this area of knowledge (15,21,27) . Extension projects conducted in clinical practice contribute to the awareness of cancer prevention actions to be carried out with the community (15,21,27) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A formação médica no Brasil, passou por mudanças consideráveis nas últimas duas décadas, com a instituição das Diretrizes Curriculares Nacionais do Curso de Graduação em Medicina 27 , que prevê a formação de um profissional generalista capaz de atuar na promoção de saúde, na prevenção e no diagnóstico das principais doenças humanas. Entretanto, o estudo de cancerologia não é suprido de maneira satisfatória na maioria das escolas médicas, criando lacunas na graduação, o que, invariavelmente, repercutem na qualidade do atendimento prestado à população, sendo esta dependente do preparo e capacitação desses futuros profissionais [11][12][13]15 . Por esta razão, as instituições de ensino superior do país devem contemplar, em seus currículos, o conhecimento integrado, contextualizado e voltado para a prevenção das doenças neoplásicas, tendo em vista o impacto do câncer na morbimortalidade da população brasileira e mundial 1,2,4 .…”
Section: Discussionunclassified
“…No entanto, os conteúdos de cancerologia ainda são limitados na maioria das escolas médicas, com uma importante parcela dos estudantes considerando insatisfatória a atenção dada para a compreensão das doenças oncológicas na estrutura curricular, o que, por sua vez, repercute na segurança autorreferida pelos discentes quanto às práticas de controle e enfrentamento das neoplasias, comparado a outras doenças comuns 12,13 .…”
unclassified